INTERFAITH MARRIAGE CONTROVERSIES IN SEMARANG: AN ANALYSIS OF QUR'ANIC LEGAL EXEGESIS - Abdul Basid; Lilik Nur Kholidah; Muhammad Fahmi Hidayatullah; Eka Kurnia Firmansyah; Ahmad Iwan Zunaih; Reza Ahmad Zahid (Malaysian Journal of Syariah and Law)
Interfaith marriage in Semarang has become a controversial issue, challenging established religious, cultural, and legal norms. The study aims to address two key questions on how Indonesian society responds to interfaith marriage and what role does the Qur'an play in the interfaith marriage controversy in Semarang. Through this study, we seek to gain an in-depth understanding of the interaction between religious teachings and social responses, with the broader aim of enhancing insights into the influence of Qur'anic exegesis on interfaith marriage dynamics. Th study adopts a qualitative approach, utilising document analysis and in-depth interviews. Primary participants include interfaith couples and Indonesian netizens. Data collection is conducted through interviews, field observations, and document analysis, including Qur'anic exegesis, religious decrees, fatwas, and public commentary. Thematic analysis is applied to identify evolving patterns in Islamic legal understanding and its impact on social harmony. In Semarang, interfaith marriage has proved to be a contentious affair for both social and legal researchers owing to some of the intricate issues it entails. Interfaith couples often experience disapproval not only from their families but society as a whole. A considerable part of society shows contempt, as per the religious views such marriages can endanger the family’s spirituality. Nevertheless, there are some who advocate for Indonesian multiculturalism and the values of respect and social harmony thus viewing interfaith marriages as legitimate. This dispute includes discussions of Qur’anic interpretation and Islamic law as they assert different viewpoints regarding the legitimacy of marriage of Muslims with Ahl al-Kitab. What aggravates the situation along with the ambiguous national legislation is the fatwa that was promulgated by Majelis Ulama Indonesia about interfaith marriages. This paper responds to the identified problems by offering some recommendations for communication, better understanding around the differences as well as the maqasid al-shari’ah objectives of protecting religion and nashab.